Drosophila Relish Activating lncRNA-CR33942 Transcription Facilitates Antimicrobial Peptide Expression in Imd Innate Immune Response - Zhou, Hongjian; Wu, Shanshan; Liu, Li; Li, Ruimin; Jin, Ping; Li, Shengjie (Frontiers in Immunology, 2022)
Long noncoding RNAs (lncRNAs) are an emerging class of regulators that play crucial roles in regulating the strength and duration of innate immunity. However, little is known about the regulation of Drosophila innate immunity-related lncRNAs. In this study, we first revealed that overexpression of lncRNA-CR33942 could strengthen the expression of the Imd pathway antimicrobial peptide (AMP) genes Diptericin (Dpt) and Attacin-A (AttA) after infection, and vice versa. Secondly, RNA-seq analysis of lncRNA-CR33942-overexpressing flies post gram-negative bacteria infection confirmed that lncRNA-CR33942 positively regulated the Drosophila immune deficiency (Imd) pathway. Mechanistically, we found that lncRNA-CR33942 interacts and enhances the binding of NF-κB transcription factor Relish to Dpt and AttA promoters, thereby facilitating Dpt and AttA expression. Relish could also directly promote lncRNA-CR33942 transcription by binding to its promoter. Finally, rescue experiments and dynamic expression profiling post-infection demonstrated the vital role of the Relish/lncRNA-CR33942/AMP regulatory axis in enhancing Imd pathway and maintaining immune homeostasis. Our study elucidates novel mechanistic insights into the role of lncRNA-CR33942 in activating Drosophila Imd pathway and the complex regulatory interaction during the innate immune response of animals.